2017
DOI: 10.1159/000452913
|View full text |Cite
|
Sign up to set email alerts
|

The Somatotrope Growth Hormone-Releasing Hormone/Growth Hormone/Insulin-Like Growth Factor-1 Axis in Immunoregulation and Immunosenescence

Abstract: Most scientific reports debate the thymotropic and immuno-stimulating properties of the somatotrope growth hormone-releasing hormone (GHRH)/growth hormone (GH)/insulin-like growth factor (IGF)-1 axis, but there is still some disagreement about the physiological role of this axis in basal conditions. Moreover, some authors have hypothesized that the physiological role of the somatotrope axis only appears in stressful conditions (such as sepsis or infective and inflammatory diseases). This chapter will provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Intriguingly, the GH–IGF1 axis and the immune system seem to be finely interconnected. In fact, it is worth recalling that GH is fundamental for the development and maintenance of the immune system, and its reduction might also lead to an immune system disruption, as recently observed in rodent models (10). Moreover, both GH and IGF1 are capable of stimulating the development of antigen‐responsive clones of B and T cells, and they can increase the survival of antigen‐responsive cells (10).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Intriguingly, the GH–IGF1 axis and the immune system seem to be finely interconnected. In fact, it is worth recalling that GH is fundamental for the development and maintenance of the immune system, and its reduction might also lead to an immune system disruption, as recently observed in rodent models (10). Moreover, both GH and IGF1 are capable of stimulating the development of antigen‐responsive clones of B and T cells, and they can increase the survival of antigen‐responsive cells (10).…”
mentioning
confidence: 89%
“…In fact, it is worth recalling that GH is fundamental for the development and maintenance of the immune system, and its reduction might also lead to an immune system disruption, as recently observed in rodent models (10). Moreover, both GH and IGF1 are capable of stimulating the development of antigen‐responsive clones of B and T cells, and they can increase the survival of antigen‐responsive cells (10). Some reports have also indicated that GH drives macrophage polarization toward an M2 anti‐inflammatory phenotype (11), and it has been suggested that the somatotropic axis may play an important role in the regulation of stressful conditions such as sepsis or infective and inflammatory diseases (9).…”
mentioning
confidence: 89%
“…This was reinforced by the observation of aged-atrophic thymus rejuvenation by GH-producing pituitary adenoma cells ( 5 ). The effects mediated by GH and IGF1 on immune cells have been extensively reviewed ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the immune system, GH stimulates the growth of primary and secondary lymphoid organs [7,8], where it induces lymphocyte proliferation and the production of cytokines and other immune factors [9,10]. In addition, GH also acts as a cytokine [11] and stimulates the innate and adaptative immune responses [12]. Moreover, GH is expressed in immune cells of various species, such as canine lymph nodes [13], human peripheral blood lymphocytes [14], rat, mouse, and bovine splenocytes [15,16], as well as in several immune cell lines (H-9 T cells and IM-9 B cells) [17].…”
Section: Introductionmentioning
confidence: 99%